FC 105LITHIUM PRESERVES PERITONEAL MEMBRANE INTEGRITY BY REDUCING MESOTHELIAL CELL ΑB-CRYSTALLIN. (29th May 2021) - Herzog, Rebecca; González, Guadalupe; Bartosova, Maria; Sacnun, Juan Manuel; Daniel-Fischer, Lisa; Vychytil, Andreas; Schmitt, Claus; López-Cabrera, Manuel; Alper, Seth; Aufricht, Christoph; Kratochwill, Klaus
Abstract: Background and Aims: Renal replacement therapy by peritoneal dialysis (PD) is limited in use and duration by progressive impairment of peritoneal membrane integrity and homeostasis. Preservation of peritoneal membrane integrity during chronic PD remains an urgent but long-unmet medical need. PD therapy failure results from peritoneal fibrosis and angiogenesis caused by hypertonic PD fluid (PDF)-induced mesothelial cytotoxicity. The incompletely defined pathophysiological mechanisms involved confound informed selection of therapeutic targets. Addition of cytoprotective agents to PDF have been shown to counteract pathophysiological mechanisms induced by current PDF. Lithium is a well described inhibitor of glycogen synthase kinase 3β and has recently been shown to also have nephroprotective effects in low doses. Here, we aim to characterize icodextrin-based, PDF-induced cellular injury with a combined omics approach and to investigate the effects of LiCl on the PD-induced observed molecular perturbations. Method: To investigate mechanisms of acute cellular damage by PDF we chose an in vitro model of primary omental-derived peritoneal mesothelial cells with direct exposure to icodextrin-based PDF, followed by short-term or extended recovery for detection of short-term and long-term changes in transcriptome, proteome, and cell injury. 0, 2.5 or 10 mM LiCl were added to the PDF. In-vitro findings were validated in peritoneal biopsies (n=41) from pediatric PD and CDK5 patients or healthy controls and peritoneal effluents from adult and pediatric PD patients (n=27) or ascites samples (n=4) as control. For in-vivo experiments, healthy and uremic mice (C57/Bl6, female) were chronically exposed to PD-fluid without or with the addition of 5 mM LiCl via an implanted catheter. In-vivo overexpression of CRYAB was induced by i.p. injection of an adenoviral vector. All animal experiments and use of patient samples were approved by the local ethics committees and performed according to animal protection laws or the Declaration of Helsinki, respectively. Results: LiCl significantly improved mesothelial cell survival in a dose-dependent manner. Combined transcriptomic and proteomic characterization of icodextrin-based PDF-induced mesothelial cell injury identified αB-crystallin as the mesothelial cell protein most significantly and consistently counter-regulated by LiCl. In-vitro and in-vivo overexpression of αB-crystallin triggered a fibrotic phenotype and PDF-like upregulation of vascular endothelial growth factor (VEGF), CD31-positive cells, and TGFβ-independent activation of TGFβ-regulated targets. In contrast, αB-crystallin knock-down decreased VEGF expression and early mesothelial-to-mesenchymal transition (MMT). LiCl reduced VEGF release and counteracted fibrosis- and angiogenesis-associated processes. αB-crystallin in patient-derived mesothelial cells was specifically upregulated in response to PDF and increased in peritoneal mesothelial cells from pediatric PD patient biopsies, correlating with markers of angiogenesis and fibrosis. Conclusion: The cytoprotective effects of LiCl-supplemented PDF may be explained by counter-regulation of PD-induced angiogenesis via the novel target αB-crystallin. Reduction of mesothelial cell damage, peritoneal fibrosis and VEGF suggests therapeutic potential of this intervention. Repurposing LiCl as a cytoprotective PDF additive may offer a translatable therapeutic strategy to combat peritoneal membrane deterioration during PD therapy. Further study of LiCl-supplemented PDF is merited as a realistic approach to improving treatment longevity and patient outcomes during PD treatment.